Failure analysis of various fiberglass cross-arm designs under multi-axial loading - Mohamad D.; Beddu S.; Syamsir A.; Zahari N.M.; Razali M.F.; Abu Seman S.A.H.; Abas A.; Ng F.C. (IOP Publishing Ltd, 2023)
This study investigated the type of failure modes of different cross-arm designs under multi-axial static loading. The failure modes were numerically predicted from real-scale finite-element models of cross-arm integrated with a Hashin damage subroutine. Three finite-element models of cross-arm were considered; a model with standard cross-arm design, a standard design engaged with braces, and a standard design engaged with sleeves. The failure analysis of the composite cross-arm was focused on the location and type of failure of the structure upon its application. This investigation revealed that under the applied load, the cross-arm with installed sleeves exhibited the lowest total deflection of 0.21 m. Every cross-arm design exhibited fiber failure due to the tension and compression mode, regardless of the support system installed. Additionally, the installation of sleeves and braces on the cross-arm structure successfully reduced the number of areas associated to failure. Published under licence by IOP Publishing Ltd.